Impact of Climate on Student Education and Their Future Development - Muzamil Hussain AL Hussaini (PT FORMOSA CENDEKIA GLOBAL, 2023)
Climate change has had a profound and lasting effect on student education and their future development. Not only does climate change have an impact on the environment, but it can also have a negative effect on educational systems, from curriculum changes to increased disruption in school buildings. To understand how climate change is affecting students, we must first look at what climate change means for our planet. As temperatures rise, natural disasters become more frequent and intense, sea levels rise, agriculture becomes riskier and more unpredictable, and extreme weather events threaten infrastructure. All of these effects have wide-reaching implications for student learning – from lack of access to resources to decreased motivation to learn due to fear of the unknown. Some Quantitative and survey study results have been draw out In this article, there is explore the impact of climate on student education and their future development